Surgical treatment of pleurocutaneous fistula in a patient 20 years after radiation therapy and breast-conserving surgery - Končar, Jovana; Novaković, Marijan; Stojiljković, Dejan; Raković, Marija; Jurišić, Vladimir; Radenković, Sandra (Vojnosanitetski pregled, 2025)
Introduction. Radiation therapy after breast-conserving surgery substantially reduces the risk of local disease recurrence and moderately reduces the risk of cancer-related death. However, long-term side effects are related to numerous factors, including patient age, comorbidities, total radiation dose, fraction size, and extent of disease. Case report. We present the case of a 61-year-old female patient who developed an ulceration at the center of a postoperative scar, accompanied by progressive tissue destruction that eventually reached 6 × 3 cm in size, resulting in rib exposure. Twenty years ago, she had a conservative surgery of the right breast due to invasive ductal carcinoma with postoperative radiation therapy to the right chest wall and the draining lymphatics. A simple mastectomy with operative removal of all sclerotic and calcified tissue, with reconstruction of the right thoracic wall, was performed by a multidisciplinary team comprising a surgical oncologist, thoracic surgeon, and plastic surgeon. The right rib cage defect of 12 × 12 cm was reconstructed with Mersilene® mesh. A large 21 × 15 cm island musculocutaneous latissimus dorsi flap was raised and transposed for reconstruction of the soft tissue defect. One thoracic and one wound drain were set in place. The postoperative course was uneventful, and the patient was discharged on the 12th postoperative day. She had no complications after a six-month follow-up. Conclusion. Long-term complications of radiation therapy are rare, but they are usually accompanied by severe consequences that require a multidisciplinary approach in complex surgical treatment.
Keywords: breast neoplasms; fistula; radiotherapy; surgical procedures, operative